1995
DOI: 10.1152/jn.1995.74.5.2087
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal activity in the ipsilateral vestibular nucleus following unilateral labyrinthectomy in the alert guinea pig

Abstract: 1. Neuronal activity was investigated in the left superior vestibular nucleus (SVN), lateral vestibular nucleus (LVN), and rostral part of the medial vestibular nucleus (MVN) in the alert guinea pig after a unilateral (left) labyrinthectomy was performed. Vestibular neurons were recorded either immediately (just-postoperative group, n = 6) or 1 wk after labyrinthectomy (1-wk-postoperative group, n = 6) and compared with the activity recorded in intact animals (control group, n = 6). 2. Animals were prepared fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
134
1
2

Year Published

1997
1997
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(147 citation statements)
references
References 0 publications
9
134
1
2
Order By: Relevance
“…It is noteworthy that intratympanic sodium arsanilate led to the degeneration of the vestibular nerve in rats (Chen et al, 1986) and that the spontaneous activity of central vestibular neurons recovers after bilateral vestibular nerve transection (Waespe et al, 1992) or unilateral surgical labyrinthectomy (Ris et al, 1995). Furthermore, Ris et al (1995) reported that despite compensatory changes after unilateral labyrinthectomy, angular head rotation failed to modulate brainstem vestibular neuron firing rates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noteworthy that intratympanic sodium arsanilate led to the degeneration of the vestibular nerve in rats (Chen et al, 1986) and that the spontaneous activity of central vestibular neurons recovers after bilateral vestibular nerve transection (Waespe et al, 1992) or unilateral surgical labyrinthectomy (Ris et al, 1995). Furthermore, Ris et al (1995) reported that despite compensatory changes after unilateral labyrinthectomy, angular head rotation failed to modulate brainstem vestibular neuron firing rates.…”
Section: Discussionmentioning
confidence: 99%
“…However, complete recovery of the spontaneous activity of central vestibular neurons has been reported 7 days after unilateral surgical labyrinthectomy in alert guinea pigs (Ris et al, 1995) and 6 months after bilateral transection of the vestibular nerve in alert rhesus monkeys (Waespe et al, 1992). Despite the potential for compensatory activity of the intact side in the unilateral labyrinthectomy studies (Kaufman et al, 1992;Ris et al, 1995), angular head rotation failed to influence expression of Fos in ipsilateral brainstem vestibular circuits (Kaufman et al, 1992) and did not modulate the firing rates of ipsilateral brainstem vestibular neurons (Ris et al, 1995). These data indicate that although unilateral surgical and arsanilate-induced labyrinthectomies disrupt rotation-induced changes in the activity of brainstem vestibular circuitry, brainstem vestibular nuclei remain intact.…”
Section: Methodsmentioning
confidence: 99%
“…After the loss of vestibular nerve afferents induced in vivo by UL, the mean resting potential of the ipsilesional MVNn should then become more hyperpolarized. In the guinea pig, there is a complete in vivo recovery of the spontaneous discharge of the deafferented MVNn during the first week of compensation (Ris et al 1995(Ris et al , 1997. On the other hand, the in vitro studies demonstrate only moderate modifications of the spontaneous resting discharge and resting membrane potential of the ipsilesional MVNn in slices taken after 1 wk of compensation, restricted to type B neurons (Him and Dutia 2001;Ris et al 2001cRis et al , 2002.…”
Section: Functional Implications Of the Long-term Changes Of The Membmentioning
confidence: 98%
“…This imbalance is responsible for the deficits triggered by the lesion. During the first week after UL, the recovery of a normal resting discharge by the ipsilesional medial VNn (MVNn) plays a key role in the disappearance of the static syndrome by restoring the balance between the activity of neurons in both vestibular nuclei (Ris et al 1995(Ris et al , 1997. Because the ipsilesional labyrinth afferents stay silent (Jensen 1979;Sirkin et al 1984), this recovery is a model of plasticity in the CNS.…”
Section: Introductionmentioning
confidence: 99%
“…After a short period, this asymmetry disappears and the behavioral syndromes caused by unilateral labyrinthectomy diminish in parallel with the physiological recovery. (Hamann and Lannou 1987;Smith Fujisawa and Takahata -26-and Curthoys 1988a,b;Ris et al 1995Ris et al , 1997Newlands and Perachio 1990a, b). To explain this physiological recovery of bilaterally symmetrical resting discharge, Vibert and his colleagues (1999) proposed that the vestibular compensation follows a "top-down" strategy: it would first rely on the external cues given by the intact sensor systems, then on an internal reorganization of the vestibular-related networks, and finally on changes in the intrinsic pacemaker properties of the vestibular neurons themselves.…”
Section: Possible Mechanisms Of Central Compensationmentioning
confidence: 99%